Faithfulness and the purpose of Hebrews : a social identity approach - Marohl, Matthew J. (James Clarke & Co., 2010)
Faithfulness and the Purpose of Hebrews offers fresh answers to several unresolved questions by employing that branch of social psychology known as social identity theory. The author of Hebrews describes the faithfulness of Jesus as prototypical and relates the faithfulness of all others to Jesus' faith. Utilizing a model of present temporal orientation, the study interprets the dynamic relationship between the antecedent faithfulness of many witnesses and the forthcoming promised rest of the addressees. The addressees of Hebrews were encouraged to understand their futures by looking to the pa.